Toward a neurobiologically informed psychiatry. Issue 1 (13th September 2017) - Strik, Werner
Schizophrenia is a severe and, at the same time fascinating disorder. It is traditionally defined as a «dissociation» of higher brain functions, which implies a modular organization of the brain up to its highest levels of organization. This short review shows how the study of the disorder is still flawed by fundamentally different definitions of the disorder, and that a consistent naturalistic approach may help to revise the vocabulary of psychiatric disorders, opening the way towards a neurobiologically informed psychiatry. Empirical studies and clinical importance supporting this novel approach are summarized.